Hubungan Tingkat Pengetahuan Ibu Post Partum tentang IMD dan Pemberian ASI di Ruangan Kebidanan Rumah Sakit Umum Daerah Karel Sadsutubun Langgur - Herlina Madubun, Henar; Darsini; Vidhiastutik, Yusiana; Puspita, Enny (PRIMA WIYATA HEALTH, 2020)
The currently recommended Early Initiation (IMD) approach is the breast crawl method where as soon as the baby born it is is placed on the mother's stomach and left to crawl to find her own mother's nipples and finally suck them without help. Goverment number 33 article 6 . In a journal in pediatrics di Ghana showing 16 % of infant deaths can be prevented thrugh breastfeeding infants fromt the first day of birth,this figure rises to 22 % if IMD is applied . Know the relation mothers about IMD and midwifery room of Karel Sadsuitubun Langgur Regional General Hospital . relationship between Post Partum’s knowledge about IMD with breastfeeding in the Midwifery Room of the Karel Sadsutubun Langgur Regional General Hospital In this study the sampel population was 50 responden ,namely all Post Partum Mothers with healthy babies at the time of this study, with incidental sampling ressearch .The research method used was observational analytic (non-experimental). The analysis was computerized using SPSS version 22 for windows . The sampling technique that is all Post Partum Mothers with healthy babies born at the time of this study. From this test results obtained x2 = 0,033 with P value = 0,000 (PR <0.05) which means that there is a significant relationship between knowledge of pregnant women about IMD with breastfeeding in the delivery room of the Karel Sadsutubun Langgur Regional General Hospital. There is a significant (significant) relationship between mother's knowledge about IMD and breastfeeding in the Midwifery Room of the Karel Sadsutubun Langgur Regional General Hospital. IMD and ASI are very important because the first milk drups after childbirth called colostrum contain high antibodies and good nutritional concantration, hygienis and economical.